AUGUST COMTE'S PRINCIPAL COMPARATION WITH VEDANTA PHILOSOPHY - Somawati, Ayu Veronika (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2023)
Philosophy is a process of conducting critical studies to acquire the truth and to know the quintessence of some particular things. An assortment of thoughts from various figures and schools emerged related to the efforts to achieve the truth. One of them is August Comte. In Hindu teachings, there are also various schools of philosophy, one of which is Vedanta philosophy. The purpose of writing this article is to attain a comparison of the main points of August Comte with Vedanta philosophy with the intention of obtaining a new perspective of knowledge. By using a qualitative descriptive method, a comparison is achieved. According to August Comte with his positivism school, valid knowledge is knowledge that comes from positive-scientific facts. Whereas according to Vedanta, the highest knowledge is the knowledge about Atman and Brahman. August Comte's positivism emphasizes surrender to society (outside); whereas according to Vedanta, surrender is done to God (Brahman) as the origin of the entire existing universe (inside).